1996
DOI: 10.1107/s010876819600794x
|View full text |Cite
|
Sign up to set email alerts
|

Atomic displacement parameters for Ni(ND3)4(NO2)2 from 9 K X-ray and 13 K time-of-flight neutron diffraction data

Abstract: Structural parameters derived from 9(1)K X-ray diffraction data and 13(1)K time-of-flight neutron diffraction data on perdeuterated tetraamminedinitronickel(II), Ni(ND3)4(NO2)2, are compared. It is shown that excellent agreement can be obtained for both positional and thermal parameters derived separately from the two experiments, provided that great care is taken in all steps of the process, including data collection, data reduction, and nuclear and electronic structure refinement. The mean difference in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 21 publications
4
48
2
1
Order By: Relevance
“…The accuracy of the model can be tested by comparing thermal parameters for the heavy atoms derived separately from the X-ray and neutron data. [12] In the present case we obtain hDU XÀN i 0.0009 2 and hU X /U N i 1.05. This demonstrates that the systematic errors are minimal, …”
Section: Methodssupporting
confidence: 52%
“…The accuracy of the model can be tested by comparing thermal parameters for the heavy atoms derived separately from the X-ray and neutron data. [12] In the present case we obtain hDU XÀN i 0.0009 2 and hU X /U N i 1.05. This demonstrates that the systematic errors are minimal, …”
Section: Methodssupporting
confidence: 52%
“…Iversen et al have shown that even in the most accurate single crystal diffraction studies there are often systematic differences between the ADPs determined separately from x-ray and neutron diffraction data. 42 Only if extreme care is taken in the experimental reduction of systematic errors and in the data analysis ͑e.g., use of flexible aspherical electron density models͒ can identical parameters be obtained. It is generally assumed that powder data are less accurate than single crystal data, and for thermal parameters, especially, single crystal neutron data rank the highest.…”
Section: Synchrotron Powder Diffraction Datamentioning
confidence: 99%
“…An indication of the data quality was obtained from the comparison of ADPs obtained independently from X-ray and neutron refinements. [51] The ADPs can absorb uncorrected systematic errors and a good agreement between the ADPs from a neutron experiment and a multipolar modeling of X-ray data therefore implies that systematic errors have been minimized. The non-hydrogen ADPs from the X-ray experiment were on average only 1 % larger than the corresponding ADPs from neutron data (hU ii (X)/U ii (N)i 1.011 (16)) .…”
Section: Tubementioning
confidence: 99%